High-sulfate water consumption determines intake and metabolic responses to protein supplementation in lambs consuming low-quality forage - Lopez, Agustin; Arroquy, Jose Ignacio; Juárez Sequeira, Ana Verónica; DiLorenzo, Nicolas; Barrionuevo, M.C.; Distel, Roberto Alejandro (2018)
Twenty Hampshire lambs (31 ± 4 kg BW) in individual metabolism cages were used in a 10-treatment by 2-period (n = 4) trial to evaluate the interaction between protein supplementation and sulfate water on intake and metabolic responses when lambs were fed low-quality grass hay (Megathyrsus maximus; 6.4% CP, 79.5% NDF). The treatment structure was a 2 × 5 factorial: 2 water qualities (WQ; low-sulfate [LS] and high-sulfate [HS]; 442 and 8,358 mg/kg total dissolved solids, respectively) and 5 soybean meal levels (SBM; 0%, 0.25%, 0.50%, 0.75%, and 1.00% BW/d). After 15 d of adaptation, periods consisted of 5 d for determination of forage and water intake, nitrogen balance, and digestion measurements (d 16 to 20) and 1 d for blood sampling and determination of ruminal hydrogen sulfide (H2S) concentration (d 21). Supplemental SBM × WQ interactions were significant for forage OM intake (P = 0.04) and total OM intake (P = 0.04), whereas a tendency was observed for total tract digestible OM intake (P = 0.07). Intake values of LS lambs were higher than those of HS lambs (P < 0.05) in only the first and second levels of SBM. Water intake increased linearly (P < 0.01) with SBM level but was not affected by WQ (P = 0.39). Water quality and SBM supplementation affected total tract OM digestibility (TTOMD; P < 0.01); LS lambs had lower TTOMD than HS lambs (P < 0.01). Plasma urea N increased linearly in response to SBM (P < 0.01) but was not affected by WQ (P = 0.11). Nitrogen balance was not affected by SBM × WQ interaction (P > 0.12), except for N utilization (N retained/N intake ratio; P < 0.01). Regardless of WQ, N intake (P > 0.01), N urine (P > 0.01), and N balance increased linearly (P > 0.01) with SBM level. Water quality adversely affected N intake and N balance, although at the highest level of SBM no differences in N balance were observed between LS and HS lambs (P = 0.85). No changes due to WQ were observed for either urea reabsorbed by kidneys (P = 0.63) or glomerular filtration rate (P = 0.30), but renal function was affected by SBM level (P < 0.01). There was a supplemental SBM × WQ interaction for ruminal H2S concentration (P < 0.01) due mainly to a greater concentration from 0.25% BW SBM in HS than in LS lambs. In conclusion, these results confirmed the existence of an interaction between sulfate water and supplemental protein, which alters intake and metabolic responses when lambs are fed low-quality grass hay.